THE INFLUENCE OF CAPITAL STRUCTURE, PROFITABILITY, AND OPERATING COSTS ON CORPORATE INCOME TAX PAYABLE (An Empirical Study on Consumer Goods Companies Listed on the Stock Exchanges of ASEAN Countries) - Diki Wahyudi; Febrian Kwarto (Transpublika Publisher, 2024)
The ASEAN region is experiencing economic growth due to increased business activities. The consumer goods sector is important for growth in local and international markets. Companies in this sector face financial challenges such as managing capital and income tax. Corporate income tax can affect overall financial performance. Governments depend on corporate income taxes to fund public goods. It is important for businesses and policymakers to understand what factors affect the amount of corporate taxes owed. Capital structure, profitability, and operational costs can impact tax liabilities and the financial stability of firms in competitive markets. The main goal of this study is to analyze the impact of capital structure, profitability, and operational costs on the level of corporate income tax payable. A quantitative approach is utilized, with information gathered from businesses listed on the ASEAN stock exchanges over a five-year period. The sample selection process involved purposive sampling, resulting in the inclusion of 50 companies and 250 data sets. The examination of the information requires the use of statistical techniques, traditional assumption checks, and testing of hypotheses. The study aims to shed light on the relationship between capital structure, profitability, operational costs, and corporate tax obligations within the ASEAN region.